Self-government and autonomy of statutory municipalities in the light of historical sources for the "provincial capital of Ljubljana" - Kambič, Marko (Lex localis, 2008)
Today, a municipality is automatically considered as a basic local self-governing (and autonomous) community. Nevertheless, we need to keep in mind that the contemporary understanding of the municipality and its regulations are the fruit of the long development that - in Central Europe - began over 150 years ago as the foundations for modern regulations were laid. This paper briefly illustrates the draft and legalbases for the modern concept of municipal administration. It focuseson the legal position of the most important statutory municipalities in the Habsburg Monarchy at which it uses the town of Ljubljana as an example. The paper also deals with the important issue of the relationship between the institutions of self-government and autonomy. Based on the analysis of the historical legal sources, it shows that local autonomy should not be equated, as is often the case, with the concept of local self-government. It further maintains that the old Austrian municipalities were at least formally autonomous and that their autonomy was limited in the interest of the state. On the basis of archive sources for Ljubljana, it ascertains that the municipality was autonomous only as far as it could choose the moment and mode of regulating certain municipal affairs and as far as it could take into account local specifics in adopting the norms, which proved to be quite sufficient under the given circumstances. Namely, the municipal autonomy was one of the factors that significantly contributed to the rise in the standard of living for the inhabitants of Ljubljana at the end of the 19th century. Last but not least, it also contributed to the victory in the struggle for the Slovenian national rights.
Keywords: avtonomija; habsburška monarhija; Ljubljana; lokalna samouprava; lokalna uprava; mesta; mestni statuti; občine; pravna zgodovina; Slovenija